2014
DOI: 10.1002/phy2.278
|View full text |Cite
|
Sign up to set email alerts
|

Regulating hippocampal hyperexcitability through GABAB Receptors

Abstract: Disturbances of GABAergic inhibition are a major cause of epileptic seizures. GABA exerts its actions via ionotropic GABAA receptors and metabotropic G protein‐coupled GABAB receptors. Malfunction of GABAA inhibition has long been recognized in seizure genesis but the role of GABAB receptors in controlling seizure activity is still not well understood. Here, we examined the anticonvulsive, or inhibitory effects, of GABAB receptors in a mouse model of hippocampal kindling as well as mouse hippocampal slices thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 86 publications
(173 reference statements)
2
13
0
Order By: Relevance
“…Although their results conflict with our result, it is likely to be due to the fact that their results focused on acute response that occurred within 30 min after irradiation at high dose (10 Gy) in both differentiated neurons and NSCs of DG. Also, some studies have reported that the seizures, one of adverse effects of radiotherapy, is caused by change of electrical impulse through the loss of GABA receptors or the abnormal increase of calcium ion channels [ 72 , 73 ]. From the results of this study and previous reports, it is possible that the abnormal changes of synaptic signaling may be associated with IR-induced brain injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Although their results conflict with our result, it is likely to be due to the fact that their results focused on acute response that occurred within 30 min after irradiation at high dose (10 Gy) in both differentiated neurons and NSCs of DG. Also, some studies have reported that the seizures, one of adverse effects of radiotherapy, is caused by change of electrical impulse through the loss of GABA receptors or the abnormal increase of calcium ion channels [ 72 , 73 ]. From the results of this study and previous reports, it is possible that the abnormal changes of synaptic signaling may be associated with IR-induced brain injuries.…”
Section: Discussionmentioning
confidence: 99%
“…GABA B Rs modulate network excitation [ 35 ] and especially NMDAR-depended activity [ 45 , 46 ]. The fact that blockade of GABA B Rs increased the proportion of slices that displayed either spfps or spfps -nmda , suggests that GABA B R-mediated transmission regulates the excitation threshold in the local circuitry as for example occurs in the subiculum [ 34 ] and control synchronous discharges [ 50 ]. Importantly, the present results show that GABA B Rs effectively control the overall network excitability in DH but not VH.…”
Section: Discussionmentioning
confidence: 99%
“…Power spectral plots were generated by averaging with 50% window overlap and a spectral resolution of 0.3 Hz. EEG spikes were considered if they displayed amplitudes of ≥6 times of standard deviations of background EEG signals and base durations of 30-70 ms (Jeffrey et al, 2013;Lang et al, 2014). To determine the dominant frequency of the hippocampal theta rhythm, spectral plots were generated from 10-s EEG segments in individual mice during the period of movement or exploration behaviors.…”
Section: Eeg Recordings and Hippocampal Stimulationmentioning
confidence: 99%
“…2013; Lang et al, 2014), thus suggesting a subtle increase of hippocampal network excitability in some post-HI mice.…”
Section: Eeg Discharges Unobserved In Post-hi Micementioning
confidence: 99%